Natural History of Malaria Infections During Early Childhood in Twins. (18th July 2022) - Gonçalves, Bronner P; Pérez-Caballero, Raúl; Barry, Amadou; Gaoussou, Santara; Lewin, Alexandra; Issiaka, Djibrilla; Keita, Sekouba; Diarra, Bacary S; Mahamar, Almahamoudou; Attaher, Oumar; Narum, David L; Kurtis, Jonathan D; et al.
Abstract: Background: The frequency and clinical presentation of malaria infections show marked heterogeneity in epidemiological studies. However, deeper understanding of this variability is hampered by the difficulty in quantifying all relevant factors. Here, we report the history of malaria infections in twins, who are exposed to the same in utero milieu, share genetic factors, and are similarly exposed to vectors. Methods: Data were obtained from a Malian longitudinal birth cohort. Samples from 25 twin pairs were examined for malaria infection and antibody responses. Bayesian models were developed for the number of infections during follow-up. Results: In 16 of 25 pairs, both children were infected and often developed symptoms. In 8 of 25 pairs, only 1 twin was infected, but usually only once or twice. Statistical models suggest that this pattern is not inconsistent with twin siblings having the same underlying infection rate. In a pair with discordant hemoglobin genotype, parasite densities were consistently lower in the child with hemoglobin AS, but antibody levels were similar. Conclusions: By using a novel design, we describe residual variation in malaria phenotypes in naturally matched children and confirm the important role of environmental factors, as suggested by the between-twin pair heterogeneity in malaria history. Abstract : Factors including host genetics and environment are thought to influence susceptibility to malaria burden. We compared malaria infection rates in twins during early childhood and show similarities in infection history within twin pairs, but not between twin pairs.